2016
DOI: 10.1161/circulationaha.115.017604
|View full text |Cite
|
Sign up to set email alerts
|

Letter by Bi et al Regarding Article, “Segmental Aortic Stiffening Contributes to Experimental Abdominal Aortic Aneurysm Development”

Abstract: We read with great interest the important article by Raaz and colleagues, who demonstrate a causal effect of segmental aortic stiffness in abdominal aortic aneurysm (AAA) formation.1 This article successfully shows how AAA initiation seems to be a story of the butterfly effect. Previously, we introduced a novel experimental model of enlarging AAA in rabbits by a combination of elastase incubation and aortic coarctation. 2 We hypothesized that hemodynamic change caused by coarctation may play an essential role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The different outcomes of AAA models are worthy of investigation, which indicated that hemodynamic change may play an essential role in the initiation and progression AAA in rabbits. [ 18 20 ] Specifically, flow disturbance and recirculation pattern was randomly distributed throughout the AAA in Group A, but concentrated in the anterior of AAA sac in Group B. This was associated with the growth rate of the AAA inner diameter [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The different outcomes of AAA models are worthy of investigation, which indicated that hemodynamic change may play an essential role in the initiation and progression AAA in rabbits. [ 18 20 ] Specifically, flow disturbance and recirculation pattern was randomly distributed throughout the AAA in Group A, but concentrated in the anterior of AAA sac in Group B. This was associated with the growth rate of the AAA inner diameter [ 21 ].…”
Section: Discussionmentioning
confidence: 99%